Structural Insight Into the Role of Mutual Polymorphism and Conservatism in the Contact Zone of the NFR5–K1 Heterodimer With the Nod Factor - Igolkina, A. A.; Porozov, Yu B.; Chizhevskaya, E. P.; Andronov, E. E. (Frontiers in Plant Science, 2018)
Sandwich-like docking configurations of the heterodimeric complex of NFR5 and K1 Vicia sativa receptor-like kinases together with the putative ligand, Nod factor (NF) of Rhizobium leguminosarum bv. viciae, were modelled and two of the most probable configurations were assessed through the analysis of the mutual polymorphisms and conservatism. We carried out this analysis based on the hypothesis that in a contact zone of two docked components (proteins or ligands) the population polymorphism or conservatism is mutual, i.e. the variation in one component has a reflected variation in the other component. The population material of 30 wild-growing V. sativa (leaf pieces) was collected from a large field (uncultivated for the past 25-years) and pooled; form this pool, 100 randomly selected cloned fragments of NFR5 gene and 100 of K1 gene were sequenced by the Sanger method. Congruence between population trees of NFR5 and K1 haplotypes allowed us to select two respective haplotypes, build their 3D structures and perform protein-protein docking. In a separate simulation, the protein-ligand docking between NFR5 and NF was carried out. We merged the results of the two docking experiments and extracted NFR5–NF–K1 complexes, in which NF was located within the cavity between two receptors. Molecular dynamics simulations indicated two out of six complexes as stable. Regions of mutual polymorphism in the contact zone of one complex overlapped with known NF structural variations produced by R. leguminosarum bv. viciae. A total of 74% of the contact zone of another complex contained mutually polymorphic and conservative areas. Common traits of the obtained two stable structures allowed us to hypothesize the functional role of three-domain structure of plant LysM-RLKs in their heteromers.